Arterial Hypertension in Adolescents: Factors of Stabilization and Progression - N.M. Korenev; L.F. Bogmat; Ye.M. Nosov; I.M. Yakovleva; V.V. Nikonova; I.N. Bessonova (Zaslavsky O.Yu., 2014)
Based on survey data of 120 adolescents with arterial hypertension it was found that with the growth of their body mass index, severity and incidence of endothelial dysfunction disorders increased (in samples of endothelium-dependent and endothelium-independent vasodilation), which are closely correlated with disturbances in blood lipid spectrum, carbohydrate and purine metabolism, and also are associated with increased levels of endothelin-1 and inflammatory factors (C-reactive protein, interleukin-6, TNF-α), as well as microalbuminuria. The findings can be used to isolate among adolescents with hypertension persons in need of more intensive supervision and treatment, with the control of lipid, carbohydrate and purine metabolism.